The Ecosystem Services and Green Infrastructure: A Systematic Review and the Gap of Economic Valuation - Ersoy Mirici, Merve (MDPI, 2022)
This study was conducted to determine the trends at the intersection of studies made on green infrastructure and ecosystem services, which have frequently become preferred in establishing urban-green space relationships in global research. Green-related concepts have frequently been used from past to present in order to neutralise the increasing pressures on urban dynamics resulting from rapid urbanisation. Green corridor, green belt, green structure, and green finger/hand concepts have been used to provide recreational opportunities, protect nature, and keep urban sprawl under control. For the last decade, however, in addition to the traditional green concepts, green infrastructure (GI) and ecosystem services (ES) have been preferred in contemporary urban planning, as they enable the integration of the ecological concerns of the landscape and the socio-political perspective. The aim of this study is to detect the trends of the green infrastructure and ecosystem services association, and to reveal these trends in the common area with the bibliometric mapping method. The economic concept and its analysing use at the intersection of green infrastructure and ecosystem services were explored with VOSviewer using the Scopus(R) database. Furthermore, the number of documents, which initially began with around 39,719 studies, was reduced by filtering through systematic reviews, to only three documents that met the economic valuation criteria. In this way, a lack of economic analyses, creating a serious research gap within the framework of green infrastructure and ecosystem services, was quantitatively determined.
Keywords: green infrastructure; ecosystem services; economic valuation; VOSviewer; bibliometric analysis